Impact of the FATF Recommendations and their Implementation on Financial Inclusion : Insights from Mutual Evaluations and National Risk Assessments - Celik, Kuntay (World Bank, Washington, DC, 2021)
Financial system safeguards against money laundering and terrorist financing are crucial for the integrity of the global financial system, but these safeguards need to be crafted in such a way that they do not negatively affect financial inclusion and disincentive the use of the formal financial system by ordinary individuals and businesses. This study examines the possible unintended consequences of the implementation of international standards on anti-money laundering, combating the financing of terrorism (AML-CFT) on financial inclusion objectives and proposes ways to address any such consequences. This examination focuses mainly on external AML-CFT compliance evaluations, so-called mutual evaluations, led by international organizations and the money laundering and terrorist financing (ML-TF) risk assessments undertaken by the countries themselves. The analysis is supplemented by interviews with officials and private sector representatives from three countries and by field experience and observations from experts. The Financial Action Task Force (FATF), the international standard setter for AML-CFT, has been devoting increasing attention to financial inclusion over the past decade, but this is not yet fully reflected in country mutual evaluations. The FATF’s increasing attention is evident in its guidance papers on financial inclusion and digital identification (ID), and in the recognition of the importance of financial inclusion in its 2019 mandate. However, coverage of financial inclusion in mutual evaluations is still uneven and mostly superficial and is not accompanied by concrete policy recommendations.